Experimental research of masonry compressive strength in the Auschwitz II - Birkenau former death camp buildings. (October 2016) - Matysek, Piotr; Stryszewska, Teresa; Kańka, Stanisław
Abstract: The paper presents the results of strength tests of brick masonry in 14 prisoner barracks located at the Auschwitz II-Birkenau former death camp. These buildings were constructed in a few months in 1941, that is in the initial phase of the extermination camp. Strength tests were conducted as part of a broad program whose purpose was to document the condition of the camp buildings being invaluable historical material objects. Due to the nature of the historical buildings a broad program has been consulted with the services of conservation. Strength tests of masonry and masonry materials (bricks and mortars) were performed on small-diameter core samples cut from the original structures of buildings in the camp. In addition, comparative tests were carried out on samples made in the laboratory. Results and their analysis made it possible to estimate the compressive strength of masonry, bricks and mortars in the brick buildings erected more than 70 years ago. The performed documentation of brick walls and identification of strength parameters are an important stage of the planned preservation process, the ultimate goal is to preserve the historic buildings for future generations. Highlights: A test method for masonry compressive strength using core samples is proposed. Small diameter core samples-application in strength tests of historical masonry Tests of masonry in the Auschwitz-Birkenau camp buildings-methodology, results